Soil coverage evaluation with calendula (Calendula officinalis L.), crotalaria (Crotalaria Sp. L.) and oat (Avena Sp. L.) in Meloidogyne Spp. control in Quito orange (Solanum quitoense Lam.) - Betancourth García, Carlos; Salazar González, Claudia; Rodriguez, Marino (Revista de Ciencias Agrícolas, 2011)
In Narino department, the area sown with quito orange (Solanum quitoense L.) is 600 ha., which show a productivity decrease, due to the pathogens attack such as root knot nematode Meloidogyne spp. Reaching incidences close to 79% and 50% losses. On the other hand, allelopathic plant species release nematotoxic compounds, nematostatics or biocides, interfering in the nematode life cycle. This research was carried out in the village La Caldera (Pasto), in order to search alternatives of root knot disease management. For it a randomized block design was used, with three replications and five treatments, which consisted of three soil coverage: Calendula (Calendula officinalis L.), Crotalaria (Crotalaria sp. L.) and oats (Avena sp. L .) which were incorporated in flowering time, chemical control (carbofuran) at sowing and every three months and a control, incidence, severity, nematode population and production were evaluated, besides a regression between production and severity and the prevalent Meloidogyne spp. species. The results showed a 100% incidence in all treatments, but a positive effect on the coverage over the severity under the nematode population decline, also, significant differences compared to control production and chemical control. Regression analysis allowed to prove that with increasing severity was significantly reduced production. Meloidogyne incognita was the most abundant specie. We conclude that the calendula, oats and Crotalaria are a viable alternative for dealing with the problem of root knot nematode.